2015
DOI: 10.1074/jbc.m115.658781
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Shape-determining Csd6 Protein from Helicobacter pylori Constitutes a New Family of l,d-Carboxypeptidase

Abstract: Background: Csd6 is one of the cell shape-determining proteins in H. pylori.Results: The active site of Csd6 is tailored to function as an l,d-carboxypeptidase in the peptidoglycan-trimming process.Conclusion: Csd6 constitutes a new family of l,d-carboxypeptidase.Significance: The substrate limitation of Csd6 is a strategy that H. pylori uses to regulate its helical cell shape and motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 81 publications
1
48
0
Order By: Relevance
“…Treatment with a muramidase and HPLC analysis of the resulting fragments was used to uncover the substrate specificity of these enzymes. In one report, the synthetic compound β‐methyl MurNAc‐ l ‐Ala‐iso‐ d ‐Glu‐ meso ‐Dap‐ d ‐Ala was shown to act as a substrate for Csd6 from H. pylori , thus providing key evidence that the enzyme can act on small‐molecule substrates . Unfortunately, the lengthy synthesis of this compound makes it unattractive for use in further studies of mechanism or inhibitor design .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Treatment with a muramidase and HPLC analysis of the resulting fragments was used to uncover the substrate specificity of these enzymes. In one report, the synthetic compound β‐methyl MurNAc‐ l ‐Ala‐iso‐ d ‐Glu‐ meso ‐Dap‐ d ‐Ala was shown to act as a substrate for Csd6 from H. pylori , thus providing key evidence that the enzyme can act on small‐molecule substrates . Unfortunately, the lengthy synthesis of this compound makes it unattractive for use in further studies of mechanism or inhibitor design .…”
Section: Introductionmentioning
confidence: 75%
“…This manuscript focuses on Csd6 ( H. pylori ) and Pgp2 ( C. jejuni ), which catalyze the second step of the “trimming” process: the cleavage of d ‐Ala from the PG tetrapeptide to give a PG tripeptide (Scheme A) . Deletion of Csd6 or Pgp2 results in mutant bacteria with a straight‐rod morphology, impaired motility in a viscous medium, and reduced pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported the crystal structures of Csd6 (HP0518 in H . pylori 26695 strain) [ 28 ], Csd4 (HP1075) [ 29 ], and Csd3 (HP0506) [ 30 ]. We have shown that H .…”
Section: Introductionmentioning
confidence: 99%
“…The helical cell shape of H. pylori is generated and maintained by the peptidoglycan (PG) cell wall (16,17). PG-modifying enzymes (Csd1, Csd2, Csd3/HdpA, Csd4, and Csd6) are required to maintain helical cell shape in H. pylori (16)(17)(18)(19)(20)(21)(22). We and others have shown that H. pylori cell shape mutants (Δcsd1 curved-rod and Δcsd3 variably c-shapedrod mutants) are attenuated in stomach colonization (16,19).…”
mentioning
confidence: 99%